Power Comparisons and Clinical Meaning of Outcome Measures in Assessing Treatment Effect in Cancer Cachexia: Secondary Analysis From a Randomized Pilot Multimodal Intervention Trial - Balstad, Trude R.; Brunelli, Cinzia; Pettersen, Caroline H.; Schønberg, Svanhild A.; Skorpen, Frank; Fallon, Marie; Kaasa, Stein; Bye, Asta; Laird, Barry J. A.; Stene, Guro B.; Solheim, Tora S. (Frontiers in Nutrition, 2021)
Background: New clinical trials in cancer cachexia are essential and outcome measures with high responsiveness to detect meaningful changes are crucial. This secondary analysis from a multimodal intervention trial estimates sensitivity to change and between treatment effect sizes (ESs) of outcome measures associated with body composition, physical function, metabolism and trial intervention. Methods: The study was a multicenter, open label, randomised pilot study investigating the feasibility of a six-week multimodal intervention (exercise, non-steroidal anti-inflammatory drugs and oral nutritional supplements containing polyunsaturated fatty acids (n-3 PUFAs) versus standard cancer care in non-operable non-small cell lung cancer and advanced pancreatic cancer. Body composition measures from computerized tomography scans and circulating biomarkers were analyzed. Results: Forty-six patients were randomised, and the analysis included 22 and 18 patients in the treatment and control groups, respectively. The between group ESs were high for bodyweight (ES=1.2, p<0.001), small for body composition and physical function (HGS) measures (ES<0.25), moderate to high for n-3 PUFAs and 25-hydroxyvitamin D (ES range 0.64 to1.37, p<0.05 for all) and moderate for serum C-reactive protein (ES=0.53, p=0.12). Analysis within the multimodal treatment group, showed high sensitivity to change for adiponectin (ES=0.86, p=0.001), n-3 PUFAs (ES >0.8, p<0.05 for all) and moderate for 25-hydroxyvitamin D (ES=0.49, p=0.03). In the control group, a moderate sensitivity to change for bodyweight (ES=-0.84, p=0.002) and muscle mass (ES=-0.67, p=0.016), and a high sensitivity to change for plasma levels of 25-hydroxyvitamin D (ES=-0.88, p=0.002) were found. Conclusion: Demonstrating high sensitivity to change and between treatment ES compared to body composition measures, bodyweight still stands out as a clinical and relevant outcome measure in cancer cachexia. Body composition and physical function measures clearly are important to address but demand large sample sizes to detect treatment group differences. Trial registration: ClinicalTrials.gov identifier: NCT01419145.